SPIRITUALITAS ISLAM DALAM SULUK WUJIL KARYA SUNAN BONANG BERDASARKAN KAJIAN SEMIOTIK - Zalikha Zalikha; Dadan Rusmana (Universitas Sebelas Maret, 2023)
Suluk Wujil is a well-known early Javanese Islamic literary work that focuses on spiritual pursuits and teachings. Wujil, a convert seeking the ultimate truth, is a symbolic person who carries crucial Sufistic teachings as well as the revelation of socio-religious discourse at the dawn of Islam in Java. This article uses three steps of semiotic reading to disclose the content of Suluk Wujil: narrative framework, primary sign discovery, and syntagmatic and paradigmatic analysis. First, the Suluk Wujils narrative plan arose from Wujil's complaint that after ten years of spiritual study in Bonang, he had failed to enter The Ultimate Truth. The statement